2015
DOI: 10.1146/annurev-food-031414-111800
|View full text |Cite
|
Sign up to set email alerts
|

Collagen and Gelatin

Abstract: Collagen and gelatin have been widely used in the food, pharmaceutical, and cosmetic industries due to their excellent biocompatibility, easy biodegradability, and weak antigenicity. Fish collagen and gelatin are of renewed interest, owing to the safety and religious concerns of their mammalian counterparts. The structure of collagen has been studied using various modern technologies, and interpretation of the raw data should be done with caution. The structure of collagen may vary with sources and seasons, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
298
0
25

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 470 publications
(325 citation statements)
references
References 136 publications
2
298
0
25
Order By: Relevance
“…Our results are in agreement with previous investigations in which oral administration of collagen-derived products has shown improvement in skin elasticity (Proksch et al, 2014;Matsumoto et al, 2006). The improvement observed in skin elasticity suggests a long-lasting positive physiological effect, in contract to effects of topical skin-care products, which increase skin elasticity predominantly by enhancing epidermal hydration (Liu et al, 2015). Moreover, treatment with eggshells has previously shown a positive effect on skin parameters such as pigmentation and hydration.…”
Section: Discussionmentioning
confidence: 92%
“…Our results are in agreement with previous investigations in which oral administration of collagen-derived products has shown improvement in skin elasticity (Proksch et al, 2014;Matsumoto et al, 2006). The improvement observed in skin elasticity suggests a long-lasting positive physiological effect, in contract to effects of topical skin-care products, which increase skin elasticity predominantly by enhancing epidermal hydration (Liu et al, 2015). Moreover, treatment with eggshells has previously shown a positive effect on skin parameters such as pigmentation and hydration.…”
Section: Discussionmentioning
confidence: 92%
“…Regenstein et al (2003) reported that scale collagen has a unique niche market related to kocher fish. More recently, the extraction of collagen from swim bladders of fish has been considered (Liu et al, 2015).…”
Section: Collagen and Gelatinmentioning
confidence: 99%
“…46 Collagen-derived peptides have been detected in plasma after ingestion of collagen. 46 Contribution of the gut microbiota to hydrolysis of both host and dietary collagen and collagen-derived peptides has not been studied in detail and may have a significant impact on the availability of these bioactive peptides for the host. In addition, we propose that the gut microbiota could complement host protein metabolism by hydrolyzing recalcitrant short peptides to release free amino acids for further use by both microbes and host.…”
Section: Introductionmentioning
confidence: 99%